Immersed in Desire: Visual Translations of Nicole Brossard’s Le désert mauve - Wroblewski, Ania (Intermédialités / Intermediality, 2023)
Since its publication in 1987, Nicole Brossard’s Le désert mauve has come to be considered a radical feminist novel about translation. While most scholarship has focused on translation as a theme and process within the novel, this article reads Brossard’s text as an invitation for intermedial collaboration that is fueled by desire. In this light, I examine American media artist Adriene Jenik’s 1997 computer art project MAUVE DESERT: A CD-ROM Translation as well as Québécois poet Simon Dumas’ multiple engagements with the work in the 2010s (including the website mauvemotel.net and a theatre adaptation featuring Brossard herself).